Las fuentes de financiamiento y su impacto en el desarrollo de las mipymes de la ciudad de Zamora - Aguilar Maza, Adriana Brigitte (2022)
The objective of this research is to "Determine the impact of the financial system on the development of MSMEs in the city of Zamora", starting from this point, the following objectives were developed: the diagnosis of the sources of financing; the diagnosis of financing through credit and its impact on micro, small and medium-sized enterprises. First of all, a brief historical overview of the origin and evolution of the financial system over time is presented, followed by a brief introduction to the topics that were of great relevance for this study, such as the financial system, MSMEs, internal and external sources of financing and credit. It is important to note that the writing of this study has a qualitative methodology and its design is descriptive and the inductive-deductive method was used. Interviews were conducted with the managers of the financial institutions and surveys were applied to Zamorano entrepreneurs, instruments that allowed the objectives of this study to be met. The results obtained show the most used sources of financing, the types of credit offered by financial institutions, and the barriers that limit access to credit for entrepreneurs. The measurement of impact was determined based on the findings of the results, using cross-tabulations. In conclusion, the banking financial system is the support for the financing of enterprises, through credit entrepreneurs can help themselves in the activities and needs that the enterprise requires for its improvement and growth.